2011
DOI: 10.1242/dev.064006
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 expression defines a subpopulation of lineage-restricted progenitors in the mammalian retina

Abstract: The mechanisms of cell fate diversification in the retina are not fully understood. The seven principal cell types of the neural retina derive from a population of multipotent progenitors during development. These progenitors give rise to multiple cell types concurrently, suggesting that progenitors are a heterogeneous population. It is thought that differences in progenitor gene expression are responsible for differences in progenitor competence (i.e. potential) and, subsequently, fate diversification. To elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 66 publications
8
134
1
Order By: Relevance
“…Of these, 200 genes were increased by more than 1.5-fold in the Dicer-CKO retinal cells (Table S1) whereas 382 genes were down-regulated by a similar amount. Many of the genes that were down-regulated in the Dicer CKO cells (Table S2) have been previously shown to be expressed in the late progenitors, e.g., Ascl1, Dll3, Hes6 and Sox9 (3,14,19) further confirming that loss of Dicer blocked the developmental progression of the progenitor cells.…”
Section: Identification Of Targets Of the Lp-mirnasmentioning
confidence: 54%
See 4 more Smart Citations
“…Of these, 200 genes were increased by more than 1.5-fold in the Dicer-CKO retinal cells (Table S1) whereas 382 genes were down-regulated by a similar amount. Many of the genes that were down-regulated in the Dicer CKO cells (Table S2) have been previously shown to be expressed in the late progenitors, e.g., Ascl1, Dll3, Hes6 and Sox9 (3,14,19) further confirming that loss of Dicer blocked the developmental progression of the progenitor cells.…”
Section: Identification Of Targets Of the Lp-mirnasmentioning
confidence: 54%
“…Lin28b is a known target of miR-125 (26) and let-7 (27), and the increase in expression of LP-miRNAs is consistent with the observed decline in Lin28b. By contrast, Ascl1 is expressed in progenitor cells only after ganglion cell production is complete (3,28) and is strongly up-regulated over these same ages. We confirmed that Prtg and Lin28b are expressed in early progenitors by immunostaining (Fig.…”
Section: Red) (O-q) Lp-mirnas Increased the Number Of Nrl+ Photorecementioning
confidence: 93%
See 3 more Smart Citations